Evaluation of Atypical Bacteria Involved in Recurrent Deterioration of Symptoms in Chronic Obstructive Pulmonary Disease - Rashid , Muhammad Noman; Laghari, Zulfiqar; Shahid, Riaz; Abro, Saleem ullah Atta; Saleem, Qurratulain; Noman, Beenish (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To evaluate the bacterial colonies involved in the recurrent deterioration of symptoms in chronic obstructive pulmonary disease (COPD) patients. METHODOLOGY: This is an observational cross-sectional study. This study was carried out at the outpatient department (OPD) and from inpatients who were admitted as an inpatient in Medical & Pulmonology wards due to severity of illness in Lyari General Hospital from March to September in 2018. Ethical approval was taken from SMBB Medical College Karachi. 120 diagnosed COPD patients with regular follow-up in OPD with written consent, and aged between 40 to 65 years from both sexes were included by non-probability consecutive sampling technique, and Subjects with age less than 40 years, Known case of allergy, asthma, on prophylactic antibiotic therapy were excluded. All information was collected on the preformed proforma. Sputum samples were collected to Dow laboratory for culture and DNA extraction. All samples were analyzed microscopically and via Polymerase chain reaction (PCR). Statistical analysis was performed by SPSS 22.0. RESULTS: 60 stable state samples and 60 aggravated condition samples were collected from subjects on treatment for COPD. Stable state samples were negative for Chlamydophila pneumoniae, Mycoplasma pneumoniae, Streptococcus, and Haemophilus DNA, however, samples showed the presence of Moraxella (n=15), Nocardia (n=3), Lactobacilli (n=5), and Legionella (n=1) DNA. In aggravated state samples Haemophilus influenza (n =11), staphylococcus aureus (n=8), staphylococcus pneumonia (n=9), E.coli (n=8), lactobacillus (n=7), Bifidobacteria (n=7), Nocardia (n=10). CONCLUSION: There is a highly unique relationship between atypical bacteria and recurrence of the severity of symptomatology in COPD. KEYWORDS: Atypical Bacteria, COPD, Moraxella, Nocardia, Lactobacilli, Bifidobacteria.